2009
DOI: 10.1164/rccm.200807-1104oc
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Suppresses Sarcoplasmic/Endoplasmic Reticulum Ca2+-ATPase Expression in Cystic Fibrosis Airways

Abstract: Rationale: Modulation of the activity of sarcoendoplasmic reticulum calcium ATPase (SERCA) can profoundly affect Ca 21 homeostasis. Although altered calcium homeostasis is a characteristic of cystic fibrosis (CF), the role of SERCA is unknown. Objectives: This study provides a comprehensive investigation of expression and activity of SERCA in CF airway epithelium. A detailed study of the mechanisms underlying SERCA changes and its consequences was also undertaken. Methods: Lung tissue samples (bronchus and bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 60 publications
(54 reference statements)
1
35
0
Order By: Relevance
“…The increase in [Ca 2 ] Ion channel DOI:http://dx.doi.org/10.7314/APJCP.2014.15.6.2559 Expression andPrognostic Role of TRPV5 andTRPV6 in NSCLC permeability and mitochondrial [Ca 2 ] could activate mitochondrial membrane permeabilization and lead to apoptosis and necrosis. In contrast, the decrease in Ca 2 contents of the endoplasmic reticulum lumen is associated with resistance to apoptosis (Ahmad et al, 2009). In this study, changes in TRPV and its association with cancer differentiation were noticed, as observed in other reports (Dhennin-Duthille et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…The increase in [Ca 2 ] Ion channel DOI:http://dx.doi.org/10.7314/APJCP.2014.15.6.2559 Expression andPrognostic Role of TRPV5 andTRPV6 in NSCLC permeability and mitochondrial [Ca 2 ] could activate mitochondrial membrane permeabilization and lead to apoptosis and necrosis. In contrast, the decrease in Ca 2 contents of the endoplasmic reticulum lumen is associated with resistance to apoptosis (Ahmad et al, 2009). In this study, changes in TRPV and its association with cancer differentiation were noticed, as observed in other reports (Dhennin-Duthille et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…Our earlier studies with environmental oxidant gas exposures revealed enhanced airway epithelial cell death and subsequent loss of SERCA activity (17,25). We also demonstrated that diseased cystic fibrosis airway epithelium with already decreased SERCA function was highly susceptible to oxidant gas exposures (17,25). SERCA dysfunction in the heart causes severe cardiac dysfunction and death in animal models (26).…”
Section: Discussionmentioning
confidence: 66%
“…Cell harvest and culture were performed using established procedures (20). Briefly, epithelial cells were removed from lower trachea and bronchi by protease XIV digestion and plated in bronchial epithelial growth medium on collagen-coated dishes.…”
Section: Human Airway Epithelial Cell Isolationmentioning
confidence: 99%
“…HAECs were isolated from tracheas and bronchi of patients dying from nonlung disease (20). Passage 1 HAECs were harvested at 80% confluence.…”
Section: Human Tracheobronchial Airway Epithelial Cells Express Tf Inmentioning
confidence: 99%